ANALISI HUBUNGAN ANTARA KUALITAS LAYANAN DAN CITRA BANK TERHADAP KEPUASAN NASABAH BANK SYARIAH - Nurfazilah Nurfazilah; Kamaruddin Arsya; Andi Khusnul Khatimah; Zindny Fahma Kafabillah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the influence of service quality (X1) and company image (X2) on customer satisfaction (Y) at Bank Syariah Indonesia (BSI) using quantitative methods and an associative approach. Data was collected through a questionnaire that had been validated and tested for reliability, with 52 respondents as the research sample. The results of the analysis show that the two independent variables have a significant positive relationship with customer satisfaction, with service quality having a strong correlation (r = 0.699, p < 0.001) and company image showing a very strong correlation (r = 0.827, p < 0.001). The ANOVA test shows a significant F value at the 95% confidence level (α = 0.05), with a Sig value. < 0.001, indicating that service quality and company image simultaneously have a significant effect on customer satisfaction. This research emphasizes the importance of managing service quality and company image in increasing customer satisfaction in the sharia banking sector.